The Issue Of Arabic Speaking Skills Among Malay Learners: What Is Missing? - Che Haron, Sueraya Binti; Abdullah, Nurazzelena; Haron, Sabrina Che; Mohamed Mokhtar, Mohd Ieruwan (Ijaz Arabi Journal of Arabic Learning, 2025)
The persistent challenges Malay learners face in acquiring Arabic speaking skills have been extensively studied for decades, yet practical solutions remain elusive. Previous research has approached this issue with the intent of solving it from various angles, including curriculum design, teaching methodologies, learning strategies, and extracurricular activities involving both educators and students, yet the problem persists essentially unchanged. This paper adopts a novel approach by examining the gaps in our efforts to address the issue. It seeks to identify where our strategies falter, what crucial elements are lacking, and where we should begin anew. Embracing the notion that returning to Arabic tradition may offer valuable insights, this study delves into Ibn Khaldun's concept of "malakah," which provides a nuanced discussion of Arabic language instruction. This approach inherently emphasizes the practical dimension of language acquisition. The study underscores the deficiencies in current approaches and proposes pragmatic solutions to bridge the gap.